Influencia del alcoholismo en el estado nutricional de las personas internas en las clínicas de rehabilitación de la ciudad de Loja - Valle Castillo, Alejandro Israel (2014)
In order to study the influence of alcohol on nutritional status was realized the present quantitative study, descriptive cross sectional in internal alcoholics in rehabilitation clinics in the city of Loja, which were 50 people in total. Data collection was through on the clinical history of the Ministry of Health the same one that was carried out to each one of the patients. It was found that the nutritional status according BMI that has predominance is the normal with a percentage of 68%, being able to conclude that the alcoholism does not have direct influence to produce Underweight or overweight. While semiological changes of nutrient deficiency disorders presented were:Bitot's spots, angular stomatitis, spongy and bleeding gums, edema of the lower limbs and pale conjunctiva that occurred more frequently in 40% of patients. In the biochemical valuation it was obtained that 30% of alcoholic patients had hematocrit securities <42% and hemoglobin <14g/dl, that which shows that approximately the population's third part in study presents anemia of origin multifactorial, being able to be one of the main causes of alteration of the metabolism of iron and folic acid deficiency. The information obtained in this investigation recommend realize preventive actions in order to strengthen and improve the perception of risk that has about of alcoholism and its influence on the nutritional state. Key Words: Alcoholism, Nutritional state, Anemia.